2018
DOI: 10.1007/s10493-018-0273-8
|View full text |Cite
|
Sign up to set email alerts
|

The multiple roles of peroxiredoxins in tick blood feeding

Abstract: Hydrogen peroxide (HO) and hydroxyl radicals (HO·) are generated through partial reduction of oxygen. The HO· are the most reactive and have a shorter half-life than HO, they are produced from comparatively stable HO through Fenton reaction. Although controlling HO· is important and biologically advantageous for organisms, it may be difficult. Ticks are obligate hematophagous arthropods that need blood feeding for development. Ticks feed on vertebrate blood containing high levels of iron. Ticks also concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In ticks, maintenance of the redox balance is achieved through a complex antioxidant system composed mostly of enzymes (Budachetri and Karim, 2015;Kumar et al, 2016;Kusakisako et al, 2018). Included in the plethora of enzymes are the GSTs.…”
Section: Discussionmentioning
confidence: 99%
“…In ticks, maintenance of the redox balance is achieved through a complex antioxidant system composed mostly of enzymes (Budachetri and Karim, 2015;Kumar et al, 2016;Kusakisako et al, 2018). Included in the plethora of enzymes are the GSTs.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have demonstrated that the knockdown of these H 2 O 2 -scavenging enzyme genes has an inhibition effect on tick blood feeding and/or reproduction (Adamson et al, 2014;Kumar et al, 2016;Kusakisako et al, 2016a). Therefore, the antioxidant enzymes controlling the H 2 O 2 concentration in ticks can be considered to be important in tick blood feeding and reproduction (Kusakisako et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the gene silencing of a selenocysteine insertion sequence (SECIS) binding protein (SBP2), involved in selenoprotein synthesis, significantly diminished the transovarial transmission of R. parkeri parasites to eggs in A. maculatum ticks (Budachetri et al, 2017a). Thus, these enzymes are also important to the vector competency of ticks with regard to horizontal transmission and transovarial transmission (Kusakisako et al, 2018a;Hernandez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation